Human pregnancy and generation of anti‐angiotensin receptor and anti‐perlecan antibodies. (12th March 2014) - Hönger, Gideon; Cardinal, Heloise; Dieudé, Mélanie; Buser, Andreas; Hösli, Irene; Dragun, Duska; Hébert, Marie‐Josée; Schaub, Stefan
Summary Non‐HLA antibodies against the angiotensin II type 1 receptor (AT1R) and the C‐terminal fragment of perlecan (i.e., LG3) are associated with the development of renal allograft rejection. It is currently unknown how humans develop anti‐AT1R or anti‐LG3 antibodies. The aim of this study was to investigate whether pregnancy—as a model of sensitization to polymorphic proteins—induces anti‐AT1R and/or anti‐LG3 antibodies. We included 104 samples from women obtained after physiologic full‐term pregnancy and 80 samples from healthy nonsensitized controls (40 women and 40 men). Both anti‐AT1R and anti‐LG3 antibody levels were lower in pregnancy samples than in controls (both P < 0.05). By multivariate analysis, male gender was an independent predictor for high anti‐AT1R antibody levels (OR 3.66, P = 0.04) and pregnancy was predictive for low anti‐LG3 antibody levels (OR 6.53, P = 0.0001). There was no correlation of anti‐AT1R with anti‐LG3 antibody levels, either in the pregnancy or in the control samples (r2 ≤ 0.03, P ≥ 0.26). In conclusion, physiologic full‐term pregnancy does not induce anti‐AT1R or anti‐LG3 antibodies and may even lower their levels. Therefore, anti‐AT1R and anti‐LG3 antibodies are likely not caused by allosensitization. The lack of correlation of anti‐AT1R with anti‐LG3 antibodies suggests different mechanisms of generation, which remain to be elucidated.